Zone of flow separation at the upstream edge of a rectangular broad-crested weir - Zachoval, Zbyněk; Mistrová, Ivana; Roušar, Ladislav; Šulc, Jan; Zubík, Pavel (Institute of Hydrology of the Slovak Academy of Sciences, Institute of Hydrodynamics of the Academy of Sciences of the Czech Republic, 2012)
The paper deals with the determination of the basic characteristics of flow at the crest of a rectangular broad-crested weir and in detail with the characteristics of flow separation at the upstream edge of the weir crest. The determination of the characteristics is made on the basis of measurement of the water surface level, the pressure head and the velocity field using the Particle Image Velocimetry method. The characteristics are expressed dimensionless in relation to the energy overflow head and the critical depth.

The paper deals with the determination of the basic characteristics of flow at the crest of a rectangular broad-crested weir and in detail with the characteristics of flow separation at the upstream edge of the weir crest. The determination of the characteristics is made on the basis of measurement of the water surface level, the pressure head and the velocity field using the Particle Image Velocimetry method. The characteristics are expressed dimensionless in relation to the energy overflow head and the critical depth.
Zone of flow separation at the upstream edge of a rectangular broad-crested weir
Keywords: Rectangular Broad-Crested Weir; Separation Zone; Separated Flow; Rectangular Broad-Crested Weir; Separation Zone; Separated Flow